Super-efficient laser hyperthermia of malignant cells with core-shell nanoparticles based on alternative plasmonic materials. (October 2019) - Kostyukov, Artem S.; Ershov, Alexander E.; Gerasimov, Valeriy S.; Filimonov, Sergey A.; Rasskazov, Ilia L.; Karpov, Sergey V.
Highlights: Alternative plasmonic materials are better for hyperthermia due to low heat capacity. The most absorbing nanoparticle is not the best for damage of malignant cells. Short laser pulses significantly increase the efficiency of hyperthermia. Abstract: New type of highly absorbing core-shell AZO/Au (aluminum doped zinc oxide/gold) and GZO/Au (gallium doped zinc oxide/gold) nanoparticles have been proposed for hyperthermia of malignant cells purposes. Comparative studies of pulsed laser hyperthermia were performed for Au nanoshells with AZO core and traditional SiO2 (quartz) core. We show that under the same conditions, the hyperthermia efficiency in the case of AZO increases by several orders of magnitude compared to SiO2 due to low heat capacity of AZO. Similar results have been obtained for GZO core which has same heat capacity. Calculations for pico-, nano- and sub-microsecond pulses demonstrate that reduced pulse duration results in strong spatial localization of overheated areas around nanoparticles, which ensures the absence of negative effects to the normal tissue. Moreover, we propose new alternative way for the optimization of hyperthermia efficiency: instead of maximizing the absorption of nanoparticles, we enhance the thermal damage effect on the membrane of malignant cell. This strategy allows to find the parameters of nanoparticle and the incident radiation for the most effective therapy.